2017
DOI: 10.1021/acs.biochem.6b01016
|View full text |Cite
|
Sign up to set email alerts
|

Islet Amyloid Polypeptide Membrane Interactions: Effects of Membrane Composition

Abstract: Amyloid formation by islet amyloid polypeptide (IAPP) contributes to β-cell dysfunction in type-2 diabetes. Perturbation of the β-cell membrane may contribute to IAPP induced toxicity. We examine the effects of lipid composition, salt and buffer on IAPP amyloid formation and on the ability of IAPP to induce leakage of model membranes. Even low levels of anionic lipids promote amyloid formation and membrane permeabilization. Increasing the percentage of the anionic lipids, POPS or DOPG, enhances the rate of amy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
151
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(173 citation statements)
references
References 89 publications
(206 reference statements)
9
151
0
13
Order By: Relevance
“…S3). CH and SM are important membrane components affecting membrane fluidity and lipid raft formation (42), and it has been reported that the presence of SM in PC-based liposomes slows (43), and the addition of CH to synthetic lipid membranes inhibits, IAPP amyloid formation (43,44). These results support the idea that SM and/or CH in healthy pancreatic EVs may help mediate the inhibitory effect on IAPP amyloid formation.…”
Section: Resultssupporting
confidence: 71%
“…S3). CH and SM are important membrane components affecting membrane fluidity and lipid raft formation (42), and it has been reported that the presence of SM in PC-based liposomes slows (43), and the addition of CH to synthetic lipid membranes inhibits, IAPP amyloid formation (43,44). These results support the idea that SM and/or CH in healthy pancreatic EVs may help mediate the inhibitory effect on IAPP amyloid formation.…”
Section: Resultssupporting
confidence: 71%
“…There is also evidence for association of membrane damage with the growth of amyloid fibrils at the membrane surface (Engel et al 2008). Changes in the composition of the model membranes, including incorporation of cholesterol demonstrated that hIAPP dye leakage from liposomes was more sensitive to membrane composition than amyloid fibril formation at the surface (Zhang et al 2017). However, the time course of sustained leakage and fibril formation are comparable which is consistent with fibrillogenesis at the membrane surface (Engel 2009, Brender et al 2011, Cao et al 2013b.…”
Section: R126 Review D Raleigh and Othersmentioning
confidence: 85%
“…Some biophysical studies that included cholesterol also employed high concentrations of anionic lipids and these can mask the effect of the sterol. Higher concentrations of cholesterol in model membranes decrease the rate of fibril formation at the surface, whereas increased POPS leads to increased rate of fibrillogenesis (Zhang et al 2017).…”
Section: R126 Review D Raleigh and Othersmentioning
confidence: 96%
See 1 more Smart Citation
“…LUVs containing 5(6)-carboxyfluorescein (Sigma-Aldrich) were prepared according to the method of Zhang and colleagues (29) and were used in vesicle permeability studies. Briefly, MLVs were prepared using the methods described above, except that 5(6)-carboxyfluorescein was dissolved in phosphate-buffered saline (PBS, pH 7.4) at a concentration of 80 mM before hydration of the lipids.…”
Section: Methodsmentioning
confidence: 99%